Insurance Consumer Protection in Case of Default by Life Insurance Companies: Civil Law and OJK Perspectives - Rachel Sabina Azzahra; Riski Ayunda; Maulana Sutan Hasibuan; Shenny Kristina Putri Sitorus; Kelvin Alvaro (ISNU Nine-Star Multidisciplinary Journal, 2025)
The failure of life insurance companies to meet their claim payment obligations is a serious problem that not only harms consumers, but also has an impact on declining public trust in the national insurance industry. The phenomenon of default shows weaknesses in legal protection for policyholders and the effectiveness of supervision of insurance companies. This study aims to analyze the form of legal protection for life insurance consumers in default cases through two main perspectives, namely civil law and regulations issued by the Financial Services Authority (OJK). The research method used is normative juridical with a legislative approach and case studies, which are analyzed qualitatively to assess the applicable legal norms. The results show that civil law provides a basis for protection through the principle of engagement and default mechanisms, but its application is often ineffective in providing legal certainty for consumers. On the contrary, OJK regulations have a more strategic role through supervision, administrative sanctions, and consumer dispute resolution mechanisms. However, legal protection still faces obstacles in the form of weak regulatory enforcement, information inequality, and low public insurance literacy. Therefore, it is necessary to strengthen the role of the OJK, establish a policy guarantee scheme, and increase financial literacy to ensure the protection of life insurance consumers in a sustainable manner.